Complex regional pain syndrome: an evolving perspective. Issue 1146 (12th November 2020) - Cutts, Steven; Gangoo, Shafat; Srinivasan, Sriram Harish; Modi, Nitin; Pasapula, Chandra; Power, Dominic
ABSTRACT: Background: Complex regional pain syndrome (CRPS) is a heterogenous and poorly understood condition that can be provoked by quite minor injuries. The symptoms and signs of CRPS persist, long after the patient has recovered from the inciting event. In some cases, there is a clear association with a peripheral nerve injury. The degree of disability produced by CRPS is often out of proportion to the scale of the original insult and the condition is associated with protracted recovery times and frequent litigation. Methods: We have performed a PubMed literature search, referenced landmark papers in the field and included a national expert in peripheral nerve injury and repair in our team of authors. Results and Conclusions: The diagnostic criteria for CRPS have changed repeatedly over the last two centuries and much of the historical literature is difficult to compare with more recent research. In this review article, we consider how our understanding of the condition has evolved and discuss its pathogenesis, its apparent heterogenicity and the various investigations and treatments available to the clinician.